ANALISIS PENGARUH SEKTOR PERTANIAN, SEKTOR PERTAMBANGAN, DAN SEKTOR INDUSTRI TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN DI INDONESIA - Ahmad Khasanatul Ikhsan; Ariusni Ariusni; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study aims to find out and analyze the influence of (1) Agricultural Sector Revenues, (2) Mining Sector Revenues (3) Industrial Sector Revenues Against income distribution inequality in Indonesia. This type of research is descriptive and associative research, namely research that describes the research variable and finds the presence or absence of influence between independent variables and dependent variables. The types of data in this study are secondary data and panel data from 2012-2016 per Province in Indonesia. Data analysis used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: Panel Regression Model, Classical Assumption Test, t Test. The estimation results show that (1) Agricultural Sector Revenues have a negative and significant effect on Inequality of Income Distribution in Indonesia, (2) Mining Sector Revenues are not significant to Income Distribution Inequality in Indonesia (3) Industrial Sector Revenues are not significant to Income Distribution Inequality in Indonesia.